ANALISIS PENGELOLAAN ANGGARAN DANA BANTUAN OPERASIONAL SEKOLAH (BOS) TERHADAP AKUNTABILITAS DAN TRANSPARANSI PELAPORAN PERTANGGUNGJAWABAN KEUANGAN DI MI. MA’ARIF SUKUN 2 KOTA MALANG - Muhammad Shofyan Tsauri; Moh. Amin; Junaidi Junaidi (Universitas Islam Malang, 2022)
The targets of this examine are: (1) making plans, (2) implementation, (3) tracking and assessment, and (4) reporting on college resource control (BOS) in public number one colleges at MI Maarif Sukun 2 Malang. The technique used is a qualitative method regarding the main, treasurer, teachers, school board and mother and father. information collection methods are interviews, observations, and report research. The effects of this have a look at show that: (1) priority is given to investment pupil activities to enhance the pleasant of education, but community participation is limited. (2) implementation consists of: (a) disbursement of price range at the beginning of the quarter; (b) The accounting process is done periodically; (c) the principles of duty and transparency are implemented; including. properly. (3) Supervision will be exercised through school principals and college principals. Implementation is evaluated by the district control group of the BTF with the aid of filling out a questionnaire once a year. (4) reviews will be sent to the BTF control each six months.Keywords: control, operational budget of the faculty.